CHANGE OF QUALITY IN SUGAR CANE (Saccharum officinarum) JUICE - Fitry Filianty, Sapta Raharja, Prayoga Suryadarma (Jurnal Teknologi Industri Pertanian, 2010)
ABSTRACT The inhibition process method of sucrose degradation in sugar cane juice was studied by adding kawao root and mangosteen bark. These two preservative agents were traditionally often used to inhibit degradation process of sugar juice. This research was conducted to characterize sugarcane juice and preservative agent (kawao root and mangosteen bark) and to analyze quality change of the juice during incubation. The results showed that the amount of sucrose was higher (10.29%), reduction sugar was 2.43% of glucose and 0.94% of fructose, acid value was 62.5 mleq and pH value was 5.1. Kawao root and mangosteen bark consist of alkaloid, flavonoid, triterpenoid and glycoside in large portion and saponin, fenolic, triterpenoid and steroid in small portion. Changing quality of sugarcane as sucrose content showed that the preservative agent addition can inhibit sucrose degradation, specifically after 80 minute. Preserved sugarcane juice quality is better than those without preservative in terms of reduction sugar content, acid total and pH value. Keywords: kawao root,  mangosteen bark, sugarcane juice, inhibition, degradation.